PH INDICATORS AND MICROCRYSTALIZATION OF ORAL LIQUID IN ADOLESCENTS OF 15-18 YEARS WHO STUDY IN DIFFERENT EDUCATIONAL INSTITUTIONS - L.F. Kaskova; V.M. Batig; I.I. Drozda; O.V. Mytchenok (Український стоматологічний альманах, 2021)
During the research it has been found that the hydrogen index and mineralizing potential of oral fluid in adolescents aged 15-18 who study in college is lower than in other study groups. The hydrogen index of college students increases slightly from 15 years to 17 years and reaches its maximum at 18 years. In schoolchildren and students of the university, an increase in the microcrystallization of oral fluid with age was observed, and in college students a decrease was noted. This indicates the need for preventative work with this cohort to identify risk factors that cause this situation.